RETROSPECTIVE ANALYSIS OF TISSUE FIXED IMMUNOREACTANTS FROM SKIN BIOPSIES OF IMMUNE VESICULOBULLOUS LESIONS MAINTAINED IN MICHEL'S MEDIUM - DR. ARUNDHATHI. S,; DR. SUNITHA. S, (International Journal of Pharma and Bio Sciences, 2014)
Diagnosis by direct immunofluorescence (DIF) requires skin biopsies with preserved immunoreactants for which biopsies are snap-frozen in liquid nitrogen or placed in Michel's fixative that facilitates transport. Retrospective study was conducted on 30 perilesional skin biopsies of immune- vesciculobullous lesions in Michel’s medium to analyse its efficiency as transport medium. DIF was performed and samples were grouped according to the number of days they had been maintained in Michel’s medium. DIF was positive in 28 cases, accounting for 93.33%. DIF was positive in 100%, 92.31% and 83.33% of biopsies even after 5, 10 and 15 days of preservation in Michel’s medium, respectively. As the number of days in transport medium increased, the intensity of immunofluorescence decreased. There was no statistical significance (>0.05) between the intensity of immunofluorescence and the number of days the biopsies were in transport medium. Michel’s medium is an efficient transport medium, when used within 15 days, in countries where DIF facilities are not available.